2013
DOI: 10.1042/bsr20130081
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation and functionality of recombinant β-glucocerebrosidase from various production systems

Abstract: The glycosylation of recombinant β-glucocerebrosidase, and in particular the exposure of mannose residues, has been shown to be a key factor in the success of ERT (enzyme replacement therapy) for the treatment of GD (Gaucher disease). Macrophages, the target cells in GD, internalize β-glucocerebrosidase through MRs (mannose receptors). Three enzymes are commercially available for the treatment of GD by ERT. Taliglucerase alfa, imiglucerase and velaglucerase alfa are each produced in different cell systems and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 32 publications
(40 reference statements)
2
81
0
7
Order By: Relevance
“…Analysis of glycosylation patterns showed that VPRIV displayed distinctly different glycan structures from Cerezyme ® (4,25,26). Global structural characterization of glycans, through either intact protein analysis (25) or total glycan release (4,26,27), indicated that the predominant glycan on VPRIV was a high-mannose type, with nine mannose units, while Cerezyme ® contained a chitobiose tri-mannosyl core glycan with fucosylation. These differences in glycosylation affected cellular internalization.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of glycosylation patterns showed that VPRIV displayed distinctly different glycan structures from Cerezyme ® (4,25,26). Global structural characterization of glycans, through either intact protein analysis (25) or total glycan release (4,26,27), indicated that the predominant glycan on VPRIV was a high-mannose type, with nine mannose units, while Cerezyme ® contained a chitobiose tri-mannosyl core glycan with fucosylation. These differences in glycosylation affected cellular internalization.…”
Section: Introductionmentioning
confidence: 99%
“…Because imiglucerase has had much longer "exposure time" than either velaglucerase or taliglucerase, the reports of late onset events are largely confined to that product. That pattern may not necessarily hold up in the future.In vitro and animal studies of differential cellular uptake of the three ERTs have been inconsistent although most studies were not done using Gaucher monocytes or macrophages or in Gaucher animal models [1,2,29,30]. In the D409V/null Gaucher mouse model, "significant differential molecular responses were observed in direct transcriptome (the set of all RNA molecules, including mRNA, rRNA, tRNA, and other non-coding RNA) comparisons from imiglucerase-and velaglucerase-treated tissues" [31].…”
mentioning
confidence: 99%
“…They are all highly purified pharmacologic recombinant human glucocerebrosidase glycoproteins produced using different technologies and derived from different cell lines: Imiglucerase (Chinese hamster ovary cell line); Velaglucerase alfa (human fibroblasts derived from a fibrosarcoma cell line); Taliglucerase (carrot root cell line). Although the conformational crystal structures of all three appear to be similar, there are minor differences in primary amino acid structure and more significant differences in glycosylation [1,2]. Globally since 1994, more than 5,000 phenotypically and genotypically diverse Gaucher disease patients have been treated with imiglucerase with an extensive observational record of efficacy and safety.…”
mentioning
confidence: 99%
“…Os asteriscos em vermelho mostram as formas de glicosilação da GCase, semelhantes à da enzima comercial, que se pretende obter ao longo do desenvolvimento desse projeto. Ressalta-se que a fucose ligada a N-acetil-glucosamina em (c) pode ou não estar presente neste core, como mostrado em (Tekoah et al, 2013). (d) GCase de interesse, que se deseja a princípio ser obtida pelo Instituto Butantan.…”
Section: Figura 1 -(A)unclassified
“…Na verdade, a enzima terapêutica apresenta uma mistura de formas glicosiladas, sendo a forma mais abundante, aquela com 3 resíduos de manose (Figura 1c). No entanto, as formas ativas que melhor se ligam-se aos receptores de manose nos macrófagos podem ter de 3-5 resíduos de manose, como as formas indicadas com * e ** na Figura 1b (Van Patten et al, 2007;Tekoah et al, 2013). Assim, a dupla deleção dos genes alg 3 e och 1 seria suficiente para a produção da glucocerebrosidase com 5 manoses terminais e a inserção e expressão da enzima α-1,2-manosidase a seguir, resultaria em uma produção da glucocerebrosidase com 3 manoses terminais, muito semelhante ao produto comercial Cerezyme ® .…”
Section: Figura 1 -(A)unclassified